A Patient with Localized Scleroderma Successfully Treated with Etretinate - Tomoko Shima; Yuki Yamamoto; Takaharu Ikeda; Fukumi Furukawa (Karger Publishers, 2014)
There are several treatment methods for localized scleroderma, but treatment is difficult when the lesion is widely distributed. We encountered a case who was treated successfully with etretinate, a vitamin A derivative. The usefulness of this agent is discussed.